Facile One‐Step Synthesis of Mesoporous Tin Oxide Hollow Spheres and Their Functionalized Nanoreactor Variants. (1st June 2016) - Zhang, Zheye; Wang, Lu; Jin, Yunxia; Xiao, Fei; Wang, Shuai
Abstract : A facile one‐step hydrothermal templating method has been developed for the effective synthesis of mesoporous tin oxide hollow spheres (SnO2 HSs) and their functionalized Pd@SnO2 nanoreactor variants. Hollow sphere formation is accompanied by self‐dissolution of silica templates under basic conditions. The Pd@SnO2 nanoreactors exhibit superior catalytic properties in gas‐ and solution‐phase reactions.